1996
DOI: 10.1016/s0006-3495(96)79439-0
|View full text |Cite
|
Sign up to set email alerts
|

Rectification of cystic fibrosis transmembrane conductance regulator chloride channel mediated by extracellular divalent cations

Abstract: We report here distinct rectification of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel reconstituted in lipid bilayer membranes. Under the symmetrical ionic condition of 200 mM KCl (with 1 mM MgCl2 in cis intracellular and 0 MgCl2 in trans extracellular solutions, pH in both solutions buffered at 7.4 with 10 mM HEPES), the inward currents (intracellular-->extracellular chloride movement) through a single CFTR channel were approximately 20% larger than the outward currents. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Second, inward rectification has been observed using cells expressing either native or recombinant wild-type human CFTR (e.g., Quinton and Reddy, 2000 ; Lansdell et al, 2000 ; Linsdell and Gong, 2002 ; this study), indicating that inward rectification is independent of the expression system used to investigate CFTR. Third, inward rectification of CFTR Cl − channels reconstituted into planar lipid bilayers was unaffected by changes in the composition of the lipid bilayer ( Zhao et al, 1996 ), suggesting that the surface charge of the membrane lipid does not affect inward rectification. Fourth, the effects of voltage on the function of the murine CFTR Cl − channel (present study) indicate that inward rectification is a common characteristic of human and murine CFTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, inward rectification has been observed using cells expressing either native or recombinant wild-type human CFTR (e.g., Quinton and Reddy, 2000 ; Lansdell et al, 2000 ; Linsdell and Gong, 2002 ; this study), indicating that inward rectification is independent of the expression system used to investigate CFTR. Third, inward rectification of CFTR Cl − channels reconstituted into planar lipid bilayers was unaffected by changes in the composition of the lipid bilayer ( Zhao et al, 1996 ), suggesting that the surface charge of the membrane lipid does not affect inward rectification. Fourth, the effects of voltage on the function of the murine CFTR Cl − channel (present study) indicate that inward rectification is a common characteristic of human and murine CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…Using excised membrane patches from baby hamster kidney (BHK) cells expressing wild-type human CFTR, Linsdell and colleagues observed similar results in some studies ( Linsdell and Hanrahan, 1999 ; Linsdell and Gong, 2002 ), but not in others (e.g., Linsdell et al, 1998 ; Linsdell and Hanrahan, 1998b ). Moreover, Zhao et al (1996) reported inward rectification of CFTR Cl − channels reconstituted into planar lipid bilayers. In this study, we investigate the mechanism of inward rectification of the CFTR Cl − channel.…”
Section: Introductionmentioning
confidence: 99%
“…A human embryonic kidney cell line (293‐EBNA, Invitrogen) was used for transfection and expression of wt and mutant CFTR proteins. The culture conditions for maintaining the HEK 293 cells were as described previously [20,21]. The parental cell line was grown to confluence in a 37°C incubator with 5% CO 2 and passaged 1:5, 2 days before gene transfer.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid bilayer membranes were formed across an aperture of ∼200 μm diameter with a lipid mixture of PS:PE:cholesterol of 6:6:1. The lipids are dissolved in decane to a concentration of 40 mg/ml [21]. The recording solutions are as follows: cis (intracellular): 200 mM CsCl, 2 mM Mg‐ATP, 10 mM HEPES‐Tris (pH 7.4) and trans (extracellular): 50 mM CsCl, 10 mM HEPES‐Tris (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%